The Role of Indonesian Language Learning in Facilitating a Multicultural Classroom at Junior High School - Ramadani, Nurhaliza; Ulfah; Yunidar; Nur'aeni, Ida (Institut Agama Islam Negeri Palopo, 2025)
This study aims to analyze how the role of Indonesian language learning as the main communication tool and unifier in multicultural classes at Junior High School. The type of research used is qualitative research. The method used in this research is descriptive method. The data collection techniques used in this research are: 1) Observation, 2) Interview, and 3) documentation. Data analysis techniques used in this research are data reduction, data presentation and conclusion drawing. Based on the results of research on the role of Indonesian language in Junior High School, researchers see the role of Indonesian language learning in multicultural classes can be seen from how to facilitate cultural interaction through the short story